Formulation, Stability and Bioequivalency Study of Prepared Salbutamol Sulphate Nebules. - Bazigha K. Al â€"Temimy; Alaa A. Abdul â€"Rasool (College of Pharmacy University of Baghdad, 2017)
Salbutamol sulphate nebules is considered as the most rapid effective route of administration for treatment of acute attacks of asthma . This study was carried out to formulate a stable formula of salbutamol nebules containing 0.1% (2.5mg / 2.5ml) of the active ingredient in a buffered solution . Stability study in different buffers at pH 3 showed that the longest shelf life was equal to 3.5 years for formula F .In addition the bioequivalency of this formula incomparison to ventolin® nebules was measured and it was equal to (± 5.2) %. Also it was found that there was no significant difference between the formula and ventolin® nebules regarding their pharmacokinetic parameters which include elimination rate constant, elimination t 0.5 and amount of the unchanged drug excreted in urine, 30 min. after administration (p<0.05) . This study may suggest that the prepared formula could be used successfully in the preparation of salbutamol sulphate nebules.